Community-Based Medications First for Opioid Use Disorder - Care Utilization and Mortality Outcomes - Banta-Green CJ; Owens MD; Williams JR; Floyd AS; Williams-Gilbert W; Kingston S (Substance Abuse and Rehabilitation, 2024)
Caleb J Banta-Green,1– 3 Mandy D Owens,1,4 Jason R Williams,1 Anthony S Floyd,1 Wendy Williams-Gilbert,1 Susan Kingston1 1Addictions, Drug & Alcohol Institute, Department of Psychiatry and Behavioral Sciences, School of Medicine, University of Washington Seattle, Seattle, WA, USA; 2Department of Health Systems and Population Health, School of Public Health, University of Washington Seattle, Seattle, WA, USA; 3Department of Epidemiology, School of Public Health, University of Washington Seattle, Seattle, WA, USA; 4Department of Psychology, University of Washington, Seattle, WA, USACorrespondence: Caleb J Banta-Green, Addictions, Drug & Alcohol Institute, Department of Psychiatry and Behavioral Sciences, School of Medicine, University of Washington, NE Pacific St Box 356560, Seattle, WA, 98195, USA, Email calebbg@uw.eduPurpose: A large treatment gap exists for people who could benefit from medications for opioid use disorder (MOUD). People OUD accessing services in harm reduction and community-based organizations often have difficulty engaging in MOUD at opioid treatment programs and traditional health care settings. We conducted a study to test the impacts of a community-based medications first model of care in six Washington (WA) State communities that provided drop-in MOUD access.Participants and Methods: Participants included people newly prescribed MOUD. Settings included harm reduction and homeless services programs. A prospective cohort analysis tested the impacts of the intervention on MOUD and care utilization. Intervention impacts on mortality were tested via a synthetic comparison group analysis matching on demographics, MOUD history, and geography using WA State agency administrative data.Results: 825 people were enrolled in the study of whom 813 were matched to state records for care utilization and outcomes. Cohort analyses indicated significant increases for days’ supply of buprenorphine, months with any MOUD, and months with any buprenorphine for people previously on buprenorphine (all results p< 0.05). Months with an emergency department overdose did not change. Months with an inpatient hospital stay increased (p< 0.05). The annual death rate in the first year for the intervention group was 0.45% (3 out of 664) versus 2.2% (222 out of 9893) in the comparison group in the 12 months; a relative risk of 0.323 (95% CI 0.11– 0.94).Conclusion: Findings indicated a significant increase in MOUD for the intervention group and a lower mortality rate relative to the comparison group. The COVID-19 epidemic and rapid increase in non-pharmaceutical-fentanyl may have lessened the intervention impact as measured in the cohort analysis. Study findings support expanding access to a third model of low barrier MOUD care alongside opioid treatment programs and traditional health care settings.Keywords: opioid use disorder, medications for opioid use disorder, multi-site study, low-barrier care, harm reduction